Analisis Tingkat Kebisingan Kegiatan Penambangan Batu Andesit CV. Handika Karya Kulon Progo Yogyakarta - Dika, Dandika Budiawan; Mycelia Paradise, S.T., M.T.; Bayurohman Pangacella Putra (Retii, 2024)
Handika Karya (CV. HK) is a company operating in andesite mining using an open pit mining system located in Kaliduka II Hamlet, Kalirejo Village, Kapanewon Kokap, Kulon Progo Regency, Yogyakarta Special Region Province. The mining operations create noise that can significantly impact the performance of the workers. To address this, it is crucial to effectively monitor and control the noise to optimize performance and safeguard the workers' hearing health. The purpose of this report is to definitively determine the noise level produced by the mining process at CV. Handika Karya, identify the primary sources of noise, and confidently establish the safe time for mining operations in compliance with regulations such as Permenaker No. 5 of 2018 and SNI 7570 of 2010 regarding noise level standards. The research site was precisely divided into three collection points (office, temporary workshop, and monitoring area), and comprehensive data collection was conducted on two different days to accurately reflect the varying mining conditions and intensities. The noise levels due to the mining operations at CV. Handika Karya, based on the worker gathering points, were conclusively determined: 83 dBA in the monitoring area on the first day, 89.3 dBA on the second day; 82.2 dBA in the workshop on the first day, 82.75 dBA on the second day; 76.12 dBA in the office on the first day, and 80.6 dBA on the second day. The noise levels produced by specific mining operations were unequivocally recorded as follows: 95 dBA during the loading operation, 81.9 dBA for 15 seconds during the blasting process, and 101.9 dBA during drilling operations, surpassing the established noise threshold value. To effectively address excessive noise, operators are confidently provided with APT (Active Noise Reduction Earmuffs) with an NRR (Noise Reduction Rating) value of 33 dB, eliminating the need for unnecessary operator changes every 1.28 hours.